HYDROTHERMAL PARATACAMITE-QUARTZ MINERALIZATION IN METAMAFIC ROCKS OF THE OCEANIC CRUST - Sharas'kin A.Ya.; Kamenetskiy V.S.; Sushchevskaya T.M.; Knyazeva S.N. (My University, 1989)
In rock samples recovered during the 5th cruise of the R/V Akademik Boris Petrov in 1986 at one of the dredging sites, we found a new type of ore mineralization hitherto unreported for oceanic regions. Because of the keen interest shown recently in the problem of oceanic ore genesis, the results of our detailed mineralogic and geochemical study of mineralized samples are discussed in this article. We thoroughly studied three basalt-diabase breccia samples, containing veinlets and nodular segregations of gray to milk-white quartz with ore mineralization. The principal ore phase is a bright dark-green mineral with a vitreous luster, forming sparse disseminations and veinlets with quartz mass, as well as microdrusy aggregates in cavities. As determined by electron-microprobe analysis, the principal components of this mineral are copper (56.8 weight percent) and chlorine (20.17), which, together with the results of X-ray phase analysis, allow it to be identified as paratacamite.